The Relationship between Organizational Culture and Employee Performance in Malaysian Commercial Banking Sector: The Role of Self-Efficacy as a Mediator - Wang Yuxin; Zahir Osman; Valliappan Raju; Siew Poh Phung (2021)
This study examines the mediating effect of self-efficacy on the relationship between organizational culture and employee performance in Malaysian commercial banking sector. The variables under study are organizational culture, self-efficacy and employee performance. The data collection approach used a web-based questionnaire that was generated and distributed to 450 commercial banks’ employees in Klang Valley, Malaysia. The 321 collected data were analyzed by using Partial Least Squares-Structural Equation Modelling (PLS-SEM) technique to analyze the proposed research hypotheses. The results showed that self-efficacy significantly mediates the relationship between organizational culture and employee performance in Malaysian commercial banking sector. The findings of this study contribute extensive inputs into the human resource management theory and enlarge the emergent literature on employee performance in Malaysian commercial banking sector. (Abstract by authors)